2022
DOI: 10.3390/ijms232113271
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of SAUR Gene Family Identifies a Candidate Associated with Fruit Size in Loquat (Eriobotrya japonica Lindl.)

Abstract: Fruit size is an important fruit quality trait that influences the production and commodity values of loquats (Eriobotrya japonica Lindl.). The Small Auxin Upregulated RNA (SAUR) gene family has proven to play a vital role in the fruit development of many plant species. However, it has not been comprehensively studied in a genome-wide manner in loquats, and its role in regulating fruit size remains unknown. In this study, we identified 95 EjSAUR genes in the loquat genome. Tandem duplication and segmental dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…SAUR was one of the early auxin responsive genes with multiple biological functions such as hypocotyl growth, stem elongation, auxin transport and light signaling(Deng et al, 2019). EjSAUR22 played an important role in regulating fruit size via affecting cell expansion, silencing EjSAUR22 led to a small fruit size and small cell size in loquat (Eriobotrya japonica L.)(Peng et al, 2022). In this study, however, we found that MdSAUR36 exhibited an inhibitory effect on mesocarp cell division and thus nal fruit size.…”
mentioning
confidence: 52%
“…SAUR was one of the early auxin responsive genes with multiple biological functions such as hypocotyl growth, stem elongation, auxin transport and light signaling(Deng et al, 2019). EjSAUR22 played an important role in regulating fruit size via affecting cell expansion, silencing EjSAUR22 led to a small fruit size and small cell size in loquat (Eriobotrya japonica L.)(Peng et al, 2022). In this study, however, we found that MdSAUR36 exhibited an inhibitory effect on mesocarp cell division and thus nal fruit size.…”
mentioning
confidence: 52%
“…Interestingly, the chromosomal distributions of the SAUR gene family in the genomes of other higher plant species, such as coffea [19], melon [21], and wax gourd [23] also confirmed our finding. Previously, the SAUR family is being explored in various higher plant species, such as potato [12], tomato [12], watermelon [13], cotton [14], moso bamboo [15], poplar [16], grape [17], apple [18], coffea [19], Chinese white pear [20], melon [21], loquat [22], wax gourd [23], peanut [24], pineapple [25], foxtail millet [26], cucumber [27], and longan [28]. More specifically, 31 and 38 members of the SAUR families have been recorded in coffea and moso bamboo [15,19].…”
Section: Identification and Annotation Of Tcsaur Genes In Cacaomentioning
confidence: 99%
“…The high occurrence of intronless genes in the TcSAUR family in cacao could be consistent with the cases reported in other plant species. For example, most SAUR genes in pineapple did not have introns [25], while 85 (out of 95) SAUR genes in loquat also contained no intron [22]. In Chinese white pear, a majority of the SAUR genes were intronless, whereas only five SAUR genes contained at least one intron [20].…”
Section: Analysis Of Gene Structures and Phylogenetic Tree Of Tcsaur ...mentioning
confidence: 99%
See 1 more Smart Citation
“…AUX/IAA genes encode transcriptional repressors of auxin-responsive genes, while genes of the GH3 family regulate the auxin pool through negative feedback [ 36 ]. SAUR genes respond rapidly to auxin stimulation and can be transcribed by auxin within minutes without de novo protein synthesis [ 37 ]. In addition, the genes of the YUC family play an important role in IAA biosynthesis to maintain the auxin concentration and regulate plant growth [ 38 ].…”
Section: Introductionmentioning
confidence: 99%